Research on the Wing-Type Antiscour Device of Pier Based on Scour Test and Numerical Simulation - Yan Wang; Xiaoli Shen; Jinchao Chen; Zhejiang Chen; Jing Liu (Advances in Civil Engineering)
In order to reduce the local scour before the antiscour device of piers, this paper proposed an improvement on a “V-type” device. That was to say, wing plates were set on the surface of the “V-type” device to enhance the diversion and reduce the local scour. To explore the protection effect of the modified device, the inclination angles of the wing plates were set to three angles, and the scour characteristics around the device were studied through the flume scour test and numerical simulation test. The results showed that the wing plates can reduce the impact force of the diving flow which was at the front end of the protective device. Besides, they could also disturb the flow around both sides of the device and weaken its sediment carrying capacity. Thus, the local scour around the device was effectively reduced. Especially, when the wing plates were 30°, the performance of reducing the local scour was the best.